1996
DOI: 10.1080/026990596124647
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine in recovery from brain injury

Abstract: A chart review of dextroamphetamine treatment in 27 traumatic brain injury patients during rehabilitation therapy suggests that amphetamine treatment enhanced the recovery and functional status of 15 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…Several research groups have demonstrated similar long-lasting beneficial effects of amphetamine on functional recovery from brain injury in animals and Man (55)(56)(57), suggesting a common mechanism related to improvement in blood flow and facilitation of repair mechanisms.…”
Section: Discussionmentioning
confidence: 91%
“…Several research groups have demonstrated similar long-lasting beneficial effects of amphetamine on functional recovery from brain injury in animals and Man (55)(56)(57), suggesting a common mechanism related to improvement in blood flow and facilitation of repair mechanisms.…”
Section: Discussionmentioning
confidence: 91%
“…Performance on placebo became more variable over time, while cognitive efficiency and performance variability improved over time in the dextroamphetamine condition. A retrospective chart review of patients with severe TBI treated with 5 to 30 mg/d of dextroamphetamine for severe attentional or initiation problems found a positive effect on attention and participation at rehabilitation in 10 of 22 subjects [63]. No neuropsychological measures were conducted.…”
Section: Neurostimulantsmentioning
confidence: 99%
“…The use of stimulants as, methylphenidate, has the most evidence to support their use in the treatment of sustained attention deficits, processing speed and more general cognitive functioning (Whyte et al, 1997(Whyte et al, , 2004. The psychostimulant, dextroamphetamine, may also have the added benefit of reducing the variability in performance in tasks of attention and working memory (Hornstein, Lennihan, Seliger, Lichtman, & Schroeder, 1996), but the studies at this time are limited. Cholinesterase inhibitors, initially developed in treating dementia, as donepezil and physostigmine, have been useful in treating the memory deficits and improving attention following TBI (Cardenas et al, 1994;Griffin et al, 2003;Taverni, Seliger, & Lichtman, 1998;Zhang et al, 2004).…”
Section: Pharmacological Treatment Of Cognitive and Neurobehavioral Imentioning
confidence: 99%